Trend of Production and Income of Hand Line Fishermen in Tulehu Village, Central Maluku District - Lisaholith, Lia Paradita Sani; Ruban, Angela; saifulgazali, saifulgazali; Kaya, Ivonne Raystika Gretha (Hasanuddin University, 2023)
Hand line fishing business can contribute to fishermen's income. Still, this business is faced with risks and uncertainties in the amount of production, one of the factors causing it is the seasonal factor. The uncertainty of the amount of production will affect the amount of income fishermen receive. This study aimed to determine the production and income trends of hand-line fishermen in Tulehu Village, Central Maluku Regency, from September to December 2022. Primary data were collected through interviews with ten fishermen and analyzed using the business income equation. The results showed that the highest level of tuna (Thunnus sp) production in December was 690kg and the lowest in September was 299kg, while the highest income was IDR26.682.084 in December and the lowest was IDR11.850.084 in September.